Campur Kode dalam Program Acara Lapor Pak! di Stasiun Televisi Trans 7 - Vikra S., Afdalu; Fatmawati, Fatmawati (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
The name for using code-mixed language must be in accordance with the function, situation and conditions of the language itself, one of which occurs in the Lapor Pak! Because there is more than one language that is often used in television shows, this results in users mixing languages which is called code mixing. This research examines code mixing in the Lapor Pak! with the research problem of what types of code mixing are in the Lapor Pak! at Trans 7 Television Station. The aim of this research is to describe, analyze, interpret and conclude the types of code mixing in the Lapor Pak! at Trans 7 Television Station. This research approach is a qualitative research approach. The method used in the research is content analysis. The collection technique in research uses listening techniques and note-taking techniques. Based on the research results of the Andhika Jadi Commander Demi "Mother" and Sujiwo Tejo episode, there are 17 data, namely the inward code mixing type, which contains 7 data, while the outward code mixing type contains 10 data. Meanwhile, in the Greg Nwokolo & Andrea Henriette Visit episode, there are 43 data, namely the inward code mixing type, which has 6 data, while the outward code mixing type has 33 data. Types of code mixing in players' speech Report Sir! at Trans 7 Television Station in the form of inward code mixing and outward code mixing.